Insulin-Containing Wound Dressing Promotes Diabetic Wound Healing Through Stabilizing HIF-1α - Yang, Peilang; Wang, Di; Shi, Yan; Li, Mingzhong; Gao, Min; Yu, Tianyi; Liu, Dan; Zhang, Jie; Wang, Jizhuang; Zhang, Xiong; Liu, Yan (Frontiers in Bioengineering and Biotechnology, 2020)
HIF-1α is seen as a major regulator during wound healing and controls many wound healing processes, such as angiogenesis, extracellular deposition, and reepithelialization. A diabetic state plays a vicious effect on wound healing, and the destabilization of HIF-1α is a non-negligible factor. Insulin-loaded silk fibroin microparticles were prepared to release insulin by covering the wounds, and this material was proven to promote wound healing in both in vitro and in vivo studies. In this work, we found that this insulin-containing wound dressing could accelerate diabetic wound healing by promoting reepithelialization, angiogenesis, and extracellular matrix, especially collagen deposition. Meanwhile, HIF-1α was stable and accumulated in insulin-containing dressing to group wound cells, which was significantly unstable in the control group. In further studies, we showed that methylglyoxal (MGO), the main form of advanced glycation end products (AGEs), accumulated significantly and caused the destabilization of HIF-1α in the diabetic state. Insulin could alleviate the MGO-induced HIF-1α unstable state and promote HIF-1α target gene expression and its downstream biological effect such as angiogenesis and wound extracellular matrix deposition.